2019
DOI: 10.4274/mirt.galenos.2018.60490
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Clinicopathological Findings and Neutrophil-to- Lymphocyte and Platelet-to-Lymphocyte Ratios in Papillary Thyroid Carcinoma

Abstract: Objectives: Inflammatory markers such as neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been recently introduced as potential biomarkers for tumor pathogenesis, development and prognosis in solid tumors. Our aim was to assess the correlation of clinicopathological features and NLR and PLR in patients with papillary thyroid carcinoma (PTC). Methods: A total of 201 papillary thyroid carcinoma patients were divided into groups with a cut-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Previous studies have evaluated the relationship between preoperative inflammation-based scores and tumor size in patients with PTC, but the results have been contradictory. Y. Ceylan's study 30 reported that a high preoperative NLR was associated with a large tumor size; similar results were also found in other studies. 17,19,22 However, in SM Kim's study, 18 a large tumor size was correlated with a high PLR instead of a high NLR, although that study included only female patients.…”
Section: Dovepresssupporting
confidence: 81%
“…Previous studies have evaluated the relationship between preoperative inflammation-based scores and tumor size in patients with PTC, but the results have been contradictory. Y. Ceylan's study 30 reported that a high preoperative NLR was associated with a large tumor size; similar results were also found in other studies. 17,19,22 However, in SM Kim's study, 18 a large tumor size was correlated with a high PLR instead of a high NLR, although that study included only female patients.…”
Section: Dovepresssupporting
confidence: 81%
“…According to the most recent studies, there are few correlations between PLR and prognosis of patients with DTC. Ceylan et al found no correlation between clinicopathologic features of PTC and PLR 23 . Ozmen et al reported that PLR and NLR are more successful indexes for diagnosis and recurrence of DTC than C-reactive protein (they included FTC, PTC and microcarcinoma).…”
Section: Discussionmentioning
confidence: 97%
“…Chen et al suggested that a low NLR (≤ 1.6) is associated with a high risk of PTC recurrence, but with a follow-up of 12.2 ± 3.8 months it is not possible to have an estimate of DFS and OS at 5 or 10 years 22 . Ceylan et al suggested an NLR cut-off value of 1.92 and a correlation between a high NLR, large tumour size and positivity of extra-thyroidal spread 23 . Seretis et al reported that an elevated preoperative mean NLR is present in patients with microcarcinoma and in DTC, and found that elevated mean NLR does not show any significant difference between patients with multifocal or unifocal microcarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in some recent studies, NLR and PLR, which are easily obtained from blood tests, significantly elevate in patients with PTC or FTC, and such results are consistent with our. 19 Ari A et al reported that NLR and PLR were higher in patients with papillary thyroid cancer than in healthy individuals, with statistically significant difference in PLR. 20 Similarly, in the current study, PLR was significantly higher in patients with PTC than in healthy individuals, and NLR was also significantly higher.…”
Section: Discussionmentioning
confidence: 98%